The rule of locus standi in administrative law / Khazatul Naima Abd Talib, Nur Asmaniza Mohammad and Wan Fatin Fashilin Wan Adeli - Abd Talib, Khazatul Naima; Mohammad, Nur Asmaniza; Wan Adeli, Wan Fatin Fashilin (Faculty of Law, 2012)
This paper focuses on the issue of locus standi which has become a major concern in public law as it often becomes a hurdle to the public spirited individuals who seek judicial review against administrative action or decision. Most of the modern countries interpreted the rule liberally. In Malaysia, the liberal approach was celebrated in many decisions such as Lim Cho Hock and Tan Sri Haji Othman Saat. However, the rule suffered a setback in 1988 as the Federal Court adopted a restrictive approach which froze the rule at pre-1977 of common law in Government v Lim Kit Siang. The restrictive approach is condemned in modern era as it does not facilitate the citizens who wish to safeguard their interest or to uphold human rights and rule of law. Hence, many cases in Malaysia were struck out by the court on the basis of lack of standing. Therefore, this research proposes that Malaysia should liberalize the rule of standing to ensure that the rule of law and rights of citizen are safeguarded. This research will also highlight the advantages and disadvantages of the two approaches. In doing so, comparison between the position of locus standi in public law action in Malaysia with England, Australia and Canada will be made.